Update on carbon fibre - Bajpai, P. (ISmithers Rapra Publishing, 2013)
Carbon fibre is the most preferred lightweight manufacturing material, and is increasingly becoming the material of choice for manufacturers around the world. Its high tensile strength, low weight and low thermal expansion have opened a world of opportunities. Everyone from elite athletes, to car enthusiasts, to the makers of passenger jets, is moving to carbon fibre. The objective of this Update is to bring together available information on the production, properties, application and future of carbon fibres. This Update will be of interest to those involved in the investigation of carbon fibr.